Does perceived overqualification lead employees to further knowledge hiding? The role of relative deprivation and ego depletion - Yeşiltaş, Murat; Arici, Hasan Evrim; Sormaz, Ümit (Emerald, 2022)
Purpose This study aims to examine how perceived overqualification (POQ) influences employee knowledge hiding (KH) behaviors. This study further investigates the mediating effect of relative deprivation (RD) and the moderating effect of ego depletion (ED), jointly leading to moderated-mediation analysis. Design/methodology/approach Having used a time lag, a total of 850 hotel employees participated in Time 1, and data was gathered from 732 hotel employees in Time 2. Using PROCESS macro, a moderated-mediation analysis was performed to examine the hypothesized relationships. Findings This study’s findings display that POQ has a positive impact on KH. Moreover, RD plays a mediating role and ED has a moderating role in the direct and indirect associations between POQ and KH. Practical implications The findings suggest that hospitality and tourism (H&T) practitioners need to structure job positions, particularly job descriptions and specifications, by considering employee qualifications. They could encourage qualified employees to participate in the decision-making process which can increase the likelihood of their knowledge sharing and naturally limit KH behaviors. Originality/value In addition to adding to the burgeoning literature on POQ in the H&T sector, this study advances research on the RD and ED theories by statistically analyzing the link between POQ and employee KH. By considering RD as a mediator, a better comprehension is provided concerning “how” POQ associates with employee KH. By introducing ED as a moderator, researchers could better understand “when” POQ significantly associates with employee KH.